Examining factors affecting blockchain adoption for process improvement in the financial services industry - Luthuli, Sandisa Zizipho (Department of Information Systems, 2023)
The focus on blockchain, thus far, has been mainly on its technicalities and less on the institutional complexities that impede its successful implementation in originations. Industries like supply chain for instance, present many issues of inefficiencies, fraud and processes which may be non-technological but still pose serious adoption challenges. Certain industries, including the financial services, banking, and supply chain, do not properly understand blockchain as a technology due to its immaturity. Furthermore, the purpose concerning the application of blockchain technology for business process improvement remains unclear. There is still opportunity within the research field to determine the visible gaps in the literature regarding the impact of using blockchain technology. A review of the literature used for this study found that using blockchain technology has promising capabilities that may improve business processes within organizations. While research on blockchain in the financial services industry is in its infancy, there are no comprehensive frameworks to guide blockchain adoption and implementation. The examinations of the different theories led to the development of an integrative framework that would help examine key factors that affect blockchain technology adoption for process improvement in the financial services industry. This was done following careful synthesis of the Social, Technological, Environmental, Economic and Political (STEEP) and the Process, Institutional, Market and Technology (PIMT) frameworks. The study adopted a quantitative method using a quantitative survey tool to test the key factors identified by the conceptual model developed. Data was collected through an online survey within IT departments of two financial services companies, with the target audience comprising of IT professionals resulting in 72 respondents having participated. This study followed an exploratory approach where existing literature was examined to understand what, how and why the identified key factors affect the adoption of blockchain technology. Furthermore, deductive reasoning was adopted as existing theoretical frameworks were identified to test the existing theory around the adoption of blockchain technology. The philosophical stances taken in this study follow that of positivism and objectivism. Through factor analysis path, the research revealed that the combined effect of Institutional factors have a perfect positive correlation with blockchain technology adoption with the most influential factor being money laundering. Although found to be insignificant, the most influential factors on environmental factors are the ability for blockchain technology to cater for sensitive personal information, confidentiality in blockchain technology, and privacy concerns. The results, however, lack tangible evidence to show that organizations deal with sensitive personal information which blockchain technology cannot cater for. This is a barrier to blockchain technology's full adoption in the financial services sector. As a consequence of these factors on the adoption of blockchain technology, financial services sector companies have adopted blockchain technology initiatives. To that end, empirical evidence from the research shows that regulatory uncertainty prevents financial services companies from adopting blockchain technology.